A Cross-Sectional International Study of Financial Literacy Among Health Care Students. - Buchtová, Barbora; Pokorná, Andrea; Chiappinotto, Stefania; Beharková, Natália; Wilhelmová, Radka; Veselá, Lenka; Ličen, Sabina; Prosen, Mirko; Karnjuš, Igor; Bayram, Aysun; Palese, Alvisa (Nursing Economic$)
A cross-sectional survey collecting data from health care students from three European nations was performed to explore the factors influencing financial literacy in a context where students attend a public university. Financial literacy is lacking, which suggests the need for education to help the next generation of health care professionals deal with increased challenges in the financial health care sector and promote financial education among patients, families, and communities.